PENGARUH SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PADA KSP KOPDIT SANGOSAY DENGAN PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI - Mario Yosefus Lasariman; Wihelmina Mitan; Siktania Maria Diliana (Jurnal Projemen UNIPA, 2025)
This study aimed to determine the influence of Accounting Information System on the quality of financial statements whit internal control as a moderating variable. This rescarch employed a quantitative descriptive method, whit data obtained through questionnaires and literatur riview. The findings indicate that the accounting information system variabel had a significan effect on the quality of financial statemens. Internal control also had a significan effect on the quality of financial statemens. Furthemore, the results showed that internal control moderated the relationship between accounting information system and the quality of financial statemens, meaning that internal control strengthened the effect of accounting information systems on the quality of financial statements. Accounting information system internal control together accounted for 89.9 percent of the variation in the quality of financial statements, while the remaining 10.1 percent was, influenced by other variables